2017
DOI: 10.1111/cdev.12760
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Early Developmental Milestones With Adult Intelligence

Abstract: The study investigated whether age at attainment of 20 developmental milestones within the areas of language, walking, eating, dressing, social interaction, and toilet training was associated with adult intelligence. Mothers of 821 children of the Copenhagen Perinatal Cohort recorded 20 developmental milestones at a 3-year examination, and all children were administered the Wechsler Adult Intelligence Scale when they were 20-34 years old. Later attainment of a number of milestones was associated with lower adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 59 publications
4
23
0
Order By: Relevance
“…Three previous longitudinal studies are based on a study design in which cognitive outcomes are measured in adulthood or adolescence: Two of these studies are based on the same birth cohort as the present study, and one study used the BPP as outcome completed at a mean follow‐up age of 19.3 years (Flensborg‐Madsen & Mortensen, ), while the other used WAIS administered at a mean adult age of 27.6 years (Flensborg‐Madsen & Mortensen, ). The studies investigated the timing of 20 developmental milestones assessed during the age from one to three years within the areas of language, walking, eating, dressing, social interaction, and toilet training, and associations were, also in these studies, analysed by multiple linear regressions adjusting for potential confounding factors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Three previous longitudinal studies are based on a study design in which cognitive outcomes are measured in adulthood or adolescence: Two of these studies are based on the same birth cohort as the present study, and one study used the BPP as outcome completed at a mean follow‐up age of 19.3 years (Flensborg‐Madsen & Mortensen, ), while the other used WAIS administered at a mean adult age of 27.6 years (Flensborg‐Madsen & Mortensen, ). The studies investigated the timing of 20 developmental milestones assessed during the age from one to three years within the areas of language, walking, eating, dressing, social interaction, and toilet training, and associations were, also in these studies, analysed by multiple linear regressions adjusting for potential confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…Although two similar subtests are included in both the BPP and the I‐S‐T 2000 R, these tests are not directly comparable, and the WAIS is a much more comprehensive measure of intelligence than the other test. However, comparison of the standardized regressions coefficients suggests that the coefficients for midlife intelligence may be at least as high as those for the BPP (Flensborg‐Madsen & Mortensen, ), while the coefficients for the WAIS may be slightly higher (Flensborg‐Madsen & Mortensen, ). Thus, it may be cautiously concluded that the present study provides no evidence that the influence of early language development is diluted over the adult life course.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Weight, length, and head increase from ages 1-3 years were calculated based on information from the 1-year and the 3-year followup. The 3-year milestones mean was calculated as the mean age of attaining 20 milestones within the areas of language, walking, eating, dressing, social interaction, and toilet training achieved between ages 1-3 years and retrospectively recalled by the mother at a 3-year examination; detailed descriptions of this data collection and the milestones can be found elsewhere [32].…”
Section: Predictor Variablesmentioning
confidence: 99%